Relationships between cross-cultural tendencies in learning and use of language learning strategies among Chinese-Malaysian and Iranian tertiary ESL learners - Omidvar, Pegah (2011)
The need for cross-cultural understanding of the relationship between culture of learning and the use of language learning strategies is becoming increasingly important because of the changing cultural mix of our classrooms and society at large. This study reports the findings on the differences between Iranian and Chinese-Malaysian learners in terms of cultural tendencies in learning, national culture and the use of language learning strategies. In addition, the relationship between cultural tendencies in learning and the use of language learning strategies is determined. A questionnaire that measures cultural tendencies in learning was developed using Hofstede’s four dimensions of national culture. The questionnaire consists of 24 items covering four dimensions: collectivism/individualism, power distance, uncertainty avoidance, and masculinity/femininity. In addition, Oxford’s Strategy Inventory for Language Learning (1980) was employed to determine the use of language learning strategies. 150 Chinese-Malaysian learners of English as a second language and 150 Iranian learners of English as a foreign language participated in the study. In terms of cultural tendencies in learning, the results showed that there were significant differences in collectivism/individualism, uncertainty avoidance and masculinity/femininity dimensions. Chinese-Malaysian had more collectivist orientations, had lower uncertainty avoidance orientations and had more tendencies towards femininism. Regarding language learning strategies, there was a significant difference in the use of metacognitive and social strategies between the two groups. Iranian learners used more metacognitive and less social strategies than the Chinese-Malaysian learners. The results of the Pearson r correlation for the Iranian learners revealed significant correlations between individualism with memory and metacognitive strategies, and collectivism with social strategies. High uncertainty avoidance was correlated with cognitive, metacognitive and affective strategies. Finally, femininity and social strategies were correlated significantly. For the Chinese-Malaysian learners, individualism was correlated with memory, cognitive and metacognitive strategies. Collectivism was correlated with social strategies. Low power distance was correlated with compensation strategies and high power distance was correlated with affective strategies. High uncertainty avoidance had correlation with cognitive strategies and low uncertainty avoidance was correlated with compensation strategies. Finally, femininism was correlated with social strategies. In conclusion, it is hard to draw conclusion about the relationship of cultural tendencies in learning and language learning strategies due to the lack of previous studies on this matter. However, the findings of the current study have served as a useful reminder that not only individual background variables (e.g., academic major and self-rated English proficiency) influence the frequency and choice of language learning strategies but also, learners’ cultural tendencies in learning could be a factor in the choice and frequency of language learning strategies amongst different cultures.